Identification and investigation of a novel NADP+-dependent secoisolariciresinol dehydrogenase from Isatis indigotica - Shi, Xiaoyi; Geng, Jiaran; Feng, Jingxian; Yang, Yingbo; Ma, Xueqi; Chen, Wansheng; Xiao, Ying (Frontiers in Plant Science, 2022)
Cofactors are crucial for the biosynthesis of natural compounds, and cofactor engineering is a use-ful strategy for enzyme optimization due to its potential to enhance enzyme efficiency. Secoisolar-iciresinol dehydrogenase (SIRD) was reported to convert secoisolariciresinol into matairesinol in an NAD+-dependent reaction. Here, a SIRD designated as IiSIRD2 identified from Isatis indigotica was found to utilize NADP+ as the cofactor. To explore the structural basis for this unique cofactor preference, model-based structural analysis was carried out, and it was postulated that a variation at the GXGGXG glycine-rich motif of IiSIRD2 alters its cofactor preference. This study paves way for future investigations on SIRD cofactor specificity and cofactor engineering to improve SIRD’s catalytic efficiency.